2004
DOI: 10.1128/aem.70.9.5252-5257.2004
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Growth of Bacillus mojavensis and Bacillus subtilis Requires Deoxyribonucleosides or DNA

Abstract: Bacillus mojavensis strains JF-2 (ATCC 39307), ROB2, and ABO21191T and Bacillus subtilis strains 168 (ATCC 23857) and ATCC 12332 required four deoxyribonucleosides or DNA for growth under strict anaerobic conditions. Bacillus licheniformis strains L89-11 and L87-11, Bacillus sonorensis strain TG8-8, and Bacillus cereus (ATCC 14579) did not require DNA for anaerobic growth. The requirement for the deoxyribonucleosides or DNA did not occur under aerobic growth conditions. The addition of a mixture of five nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 33 publications
0
12
1
3
Order By: Relevance
“…In contrast to the observation made by several groups that investigated the anaerobic metabolism of B. subtilis, recently it was found that anaerobic growth of Bacillus mojavensis and B. subtilis 168 requires externally supplied deoxyribonucleosides or DNA (7). This finding and the presence of only the oxygendependent class I RNR encoded by the B. subtilis nrdEF genes gave rise to the question of how B. subtilis is able to grow under anaerobic conditions.…”
contrasting
confidence: 46%
See 1 more Smart Citation
“…In contrast to the observation made by several groups that investigated the anaerobic metabolism of B. subtilis, recently it was found that anaerobic growth of Bacillus mojavensis and B. subtilis 168 requires externally supplied deoxyribonucleosides or DNA (7). This finding and the presence of only the oxygendependent class I RNR encoded by the B. subtilis nrdEF genes gave rise to the question of how B. subtilis is able to grow under anaerobic conditions.…”
contrasting
confidence: 46%
“…␤-Galactosidase activity was determined as described previously (10) and was expressed in Miller units (27). (7). In contrast to this observation, several other investigations during the last decade elucidated the exact nature of anaerobic nitrate respiratory and fermentative growth (4,11,12,24,29,32).…”
Section: Methodsmentioning
confidence: 55%
“…The moderate but significant reduction of virulence seen for the 6-26 mutant could suggest either a spatial or temporal gradient of oxygen within the vegetation or a partial ability to overcome the loss of anaerobic RNR activity. Some Bacillus species that apparently possess only class I RNRs can use external DNA as a source of deoxyribonucleotides under anaerobic conditions, thereby overcoming the requirement for anaerobic ribonucleotide reduction (19). Given that S. sanguinis is also naturally competent and that the biofilm of the vegetation may represent a site of increased natural competence (39), DNA uptake may have aided the survival of the RNR mutants in the CI assays.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that B. subtilis should be able to grow anaerobically using nitrate instead of oxygen as an electron acceptor. Anaerobic growth of B. subtilis in the presence of nitrate has since been demonstrated experimentally 25 . The discovery that B. subtilis can indeed grow anaerobically further supports the idea that vegetative life within the mostly anaerobic GI tract of animals is feasible.…”
Section: What Can Genomics Teach Us About B Subtilis Ecology?mentioning
confidence: 99%